Sensitivity Enhancement in Uranium Determination by UV-Visible Spectroscopy Using Ion Imprinted Polymer - Bicim, Tulin; Yaman, Mehmet (Office Spectroscopy & Spectral Analysis, 2016)
There is need to determination of uranium concentration at ppb level in environmental matrices. Due to low sensitivity of FAAS, UV-Visible Spectroscopy is generally used as measurement technique. In this study, ion-imprinted polymers (IIP) were prepared for uranyl ion ( imprint ion) by formation of ternary (salicylaldoxime and 4-vinylpyridine) complex in 2-methoxy ethanol (porogen) following copolymerization with methacrylic acid (MAA) as a functional monomer and ethylene glycol dimethacrylate (EGDMA) as crosslinking monomer using 2,2-azobisisobutyronitrile as initiator. The synthesized polymers were characterized by FTIR and TGA analysis. Arsenazo III in 3 M HClO4 was used as complexing agent in the measurement step. The optimal pH for preconcentration was found to be between 3.5 similar to 6.5 values. The developed method was applied to uranium (VI) determination in natural water samples.
Keywords: Uranium; Ion imprinted polymer; Arsenazo III; UV-vis Spectroscopy